Popular medicine in Graeco-Roman antiquity : explorations - Harris, William V. (William Vernon) (Columbia studies in the classical tradition, 2016)
The history of healthcare in the classical world suffers from notable neglect in one crucial area. While scholars have intensively studied both the rationalistic medicine that is conveyed in the canonical texts and also the 'temple medicine' of Asclepius and other gods, they have largely neglected to study popular medicine in a systematic fashion. This volume, which for the most part is the fruit of a conference held at Columbia University in 2014, aims to help correct this imbalance. Using the full range of available evidence - archaeological, epigraphical and papyrological, as well as the literary texts - the international cast of contributors hopes to show what real people in Antiquity actually did when they tried to avert illness or cure it.